DETERMINAN AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wulan Indah Sari Sinaga; Reza Hanafi Lubis (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2023)
The objective of the research was to determine the "Determinants of Tax Aggressiveness in Manufacturing Companies Listed on the Indonesia Stock Exchange". The type of research used was quantitative research. The population in this research was 193 manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The method used to determine the sample was purposive sampling with a sample of 70 companies for 3 consecutive years. The data collection method was to use documentation by taking financial statement data on the Indonesia Stock Exchange. Data that was ready to be processed would be tested using the SPSS 25 program. Based on the results of the research shows that: (1) Liquidity had no positive influence on tax aggressiveness; (2) Leverage had a positive influence on tax aggressiveness; (3) Profitability had no positive influence on tax aggressiveness; (4) The size of the company had no positive influence on tax aggressiveness. Based on the F test liquidity, leverage, profitability, and company size had a positive influence on tax aggressiveness.